Education and political and social control of the state: School visitors in Tacna and Arica (1880-1900) - Pizarro Pizarro, Elías; Bustos González, Raúl (Sociedad de Historia de la Educación Latinoamericana y la Universidad Pedagógica y Tecnológica de Colombia, 2015)
This article aims to contribute to the visibility of unknown actors of regional history in northern Chile , by analyzing documentary sources literal and logical approach , they are presented the functions accomplished by the visitors of schools as agents of educational planned action from the State and as a mechanism of political and social control, during the period of military integration in the area of Arica (1880) and its annexation to the Chilean sovereignty (1929), all this marked by a process of national historiography known as " Chilenización".